The impact of working condition, working motivation and training on employee performance in Rotol Food Chain (M) SDN BHD - Sasikala, Sivagi Ganesan (2024)
The purpose of this research paper is to investigate the working condition, working motivation and training that effects employee performance with focus on Rotol Food Chain (M) SDN BHD. The research used a descriptive research design in analysing, interpreting and presenting data. This research is important because it can help to find the employee’s performance of Rotol Food Chain (M) SDN BHD. A designed questionnaire was distributed to 200 employees who are working at this company. The respondents are selected view random sampling techniques. The data were analysed using Statistical Package for the Social Science (SPSS) software version of 27. For the data interpretation researcher used descriptive statistics of simple percentage, mean and standard deviation. In the findings there is a positive relationship between working condition, working motivation and training towards employee performance. With the help of this contributions, top management can focus on the factors that actually influence on employee performance. Therefore, it can be suggested that the Management should improve the policies in enhancing performance by managing wellness programs and reward systems that will improve employee performance in the future. Comfortable and ergonomic office furniture also important for maintain performance by comfortable seating, desk, and workstations can help reduce fatigue and discomfort and improve employee performance. Moreover, future research can focus on remote working schedules, ergonomic workplace design, training and development for the employees.